Improving The Learning Outcomes of Fiqh Fasting Worship Material Through The Problem Based Learning Method Assisted By Projected Motion Media - Maleha, Maya; Cahyono, Guntur (Fahmina: Jurnal Pendidikan Islam, 2023)
Learning Islamic Religious Education in Fiqh subjects, especially fasting material. Student learning achievement still shows a low level. This is a major concern due to the low interest and motivation of students towards these subjects. The lack of variety in learning methods and media applied by teachers means that learning feels boring, students pay less attention to learning, and students find it difficult to understand the material. The method used in research is in the form of Classroom Action Research (PTK), where data collection techniques are in the form of observation, tests, interviews and documentation. The methods used are effective learning methods and media that are adapted to the material and learning objectives. To overcome this problem, creativity is needed and several steps must be implemented by teachers to create interesting and enjoyable learning activities, one of which is by using effective learning methods and media that are adapted to the material and learning objectives. The alternative teaching method that can be applied in the process of learning fasting material in Fiqh is the Problem Based Learning (PBL) method combined with the use of Projected Motion Media. The final result of using the Problem Based Learning Method assisted by Projrcted Motion media can improve the learning outcomes of jurisprudence material on fasting for students in class VIII A MTsS Sudirman Getasan, Semarang Regency, academic year 2023/2024.